2017
DOI: 10.1111/maps.12949
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical study of brown olivine in Northwest Africa 1950 shergottite and implications for the formation mechanism of iron nanoparticles

Abstract: Martian meteorites, in particular shergottites, contain darkened olivine (so‐called “brown olivine”) whose color is induced by iron nanoparticles formed in olivine during a shock event. The formation process and conditions of brown olivine have been discussed in the Northwest Africa 2737 (NWA 2737) chassignite. However, formation conditions of brown olivine in NWA 2737 cannot be applied to shergottites because NWA 2737 has a different shock history from that of shergottites. Therefore, this study observed brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 34 publications
5
29
1
Order By: Relevance
“…Takenouchi et al. () proposed olivine darkening process and P–T – t conditions by observing brown olivine in NWA 1950 shergottite whose shock history may be simple compared to NWA 2737. Takenouchi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Takenouchi et al. () proposed olivine darkening process and P–T – t conditions by observing brown olivine in NWA 1950 shergottite whose shock history may be simple compared to NWA 2737. Takenouchi et al.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, however, Nyquist et al (2001) reported that a considerable portion of Martian meteorites do not have a sign of shock-heating. This might come from the fact that the geochemical barometers, such as shock melted glasses (e.g., Fritz et al, 2017) and atomic diffusion (e.g., Takenouchi et al, 2017), for the estimation of the temperature rise have relatively low sensitivities at a moderate temperature (several hundred K).…”
Section: Sterilization During Mars Ejecta Formationmentioning
confidence: 99%
“…The poikilitic textures are comprised of medium-to coarse-pyroxene oikocrysts that partly or completely enclose multiple olivine and spinel chadacrysts ( Fig. 1a Ikeda, 1997;Usui et al, 2010;Jiang and Hsu, 2012;Howarth et al, 2014;Combs et al, 2018 and formation of shock veins and melt pockets (e.g., McSween et al, 1979;Harvey et al, 1993;Treiman et al, 1994;Gleason et al, 1997;Gillet et al, 2005;Mikouchi, 2005;Walton and Herd, 2007;Mikouchi and Kurihara, 2008;Usui et al, 2010;Jiang and Hsu, 2012;Walton et al, 2012;Howarth et al, 2014;Takenouchi et al, 2017;Combs et al, 2018). As ALHA 77005, LEW 88516, RBT 04261/2, NWA 7397, NWA 7755, and NWA 10169 have all been previously described (e.g., Harvey et al, 1993;Treiman et al, 1994;Walton and Herd, 2007;Usui et al, 2010;Howarth et al, 2014;Combs et al, 2018, respectively) (Treiman et al, 1994;Usui et al, 2010;Howarth et al, 2014;Combs et al, 2018 vol.%, 6.4 vol.%, and 4.4 vol.%, respectively (Table 1).…”
Section: Petrographymentioning
confidence: 99%
“…The most prevalent shock feature found in shergottite meteorites is the phase transformation of plagioclase to the diaplectic glass maskelynite (e.g., Fritz et al, 2005;Fritz et al, 2017 , McSween and Stöffler, 1980;Keller et al, 1992;Nyquist et al, 2001;Fritz et al, 2005). An additional shock effect on poikilitic shergottite minerals is the darkening/browning of olivine grains, which specific causal process has been highly debated (e.g., Treiman et al, 2007;Van de Moortéle et al, 2007a;Blä et al, 2010;Takenouchi et al, 2017;, but is attributed to the precipitation of iron nanoparticles within the olivine structure upon shock (e.g., Takenouchi et al, 2017;. Darkened olivine is found within NWA 10618, NWA 11043, NWA 11065, and NWA 10961, similar to other poikilitic shergottites, such as ALHA 77005, LEW 88516, and NWA 1950 (e.g., Ostertag et al, 1984;Gillet et al, 2005;Mikouchi et al, 2005;Takenouchi et al, 2017;.…”
Section: Shock Meltingmentioning
confidence: 99%
See 1 more Smart Citation